Distribution of Gene Mutations Associated with Familial Normosmic Idiopathic Hypogonadotropic Hypogonadism - KOTAN, LEMAN DAMLA; Mengen, Eda; GÜRBÜZ, FATİH; Siklar, Zeynep; Berberoglu, Merih; Dokmetas, Sebila; Kilicli, Mehmet Fatih; GUVEN, Ayla; Kirel, Birgul; Saka, Nurcin; Poyrazoglu, Sukran; Cesur, YAŞAR; et al. (My University, 2012)
Objective: Normosmic idiopathic hypogonadotropic hypogonadism (nIHH) is characterized by failure of initiation or maintenance of puberty due to insufficient gonadotropin release, which is not associated with anosmia/hyposmia. The objective of this study was to determine the distribution of causative mutations in a hereditary form of nIHH. Methods: In this prospective collaborative study, 22 families with more than one affected individual (i.e. multiplex families) with nIHH were recruited and screened for genes known or suspected to be strong candidates for nIHH. Results: Mutations were identified in five genes (GNRHR, TACR3, TAC3, KISS1R, and KISS1) in 77% of families with autosomal recessively inherited nIHH. GNRHR and TACR3 mutations were the most common two causative mutations occurring with about equal frequency. Conclusions: Mutations in these five genes account for about three quarters of the causative mutations in nIHH families with more than one affected individual. This frequency is significantly greater than the previously reported rates in all inclusive (familial plus sporadic) cohorts. GNRHR and TACR3 should be the first two genes to be screened for diagnostic purposes. Identification of causative mutations in the remaining families will shed light on the regulation of puberty.
Keywords: Mutation; Normosmic idiopathic hypogonadotropic hypogonadism; Gene